Study of the synergy effect of high-intensity aluminum ions implantation into titanium and energy impact on the surface; Materials. Technologies. Design; Т. 5, № 3 (13) - Ryabchikov A. I. Aleksandr Ilyich; Korneva O. S. Olga Sergeevna; Kurzina I. A. Irina Aleksandrovna; Tarbokov V. A. Vladislav Aleksandrovich (2023, 2023)
Title screen